Legal Politics of Government Regulation on Creative Economy Implementation in Indonesia - Bayu Mogana Putra (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This scientific work will focus on the legal politics of Government policy through the actualisation of creative economy arrangements stipulated in Government Regulation Number 24 of 2022 concerning the Implementation Regulations of Law Number 24 of 2019 concerning the Creative Economy. The purpose to be achieved in the preparation of this scientific work is to be able to know and understand the legal politics of the implementation of the creative economy ecosystem regulated through Government Regulations as an implementing regulation of the Creative Economy Law. The method used to achieve these objectives is to use normative research methods through a statutory approach by examining in depth the implementation of the creative economy ecosystem through the Creative Economy Government Regulation. Thus the study in this scientific work can reveal the philosophical, sociological, and juridical dynamics of creative economic arrangements related to the creative economy ecosystem which includes Creative Economy Financing, Facilitating the development of Intellectual Property-Based Creative Economy Product Marketing Systems, Creative Economy Infrastructure, Incentives for Creative Economy Actors, Government and / or Regional Government responsibilities and community participation in the development of the Creative Economy, and Settlement of financing disputes.